Inclusão educacional e autismo: um estudo sobre as práticas escolares - Guareschi, Taís (2016)
The present thesis aimed at investigating the school practices created in the inclusion of students with autism, in Early Childhood education and Early Years of Elementary School, in municipal schools in Santa Maria/RS. The concept of school practices is understood as set of actions, developed by schools, which yields education. These actions include the pedagogical practices, the processes of socialization, and the pedagogical dynamics (organization of school time and spaces). In light of this, it was established a dialogue between the fields of Special Education and Psychoanalysis. The interlocution between these two areas lead to two basic theoretical assumptions. The first one is the understanding of child development as posited by Coriat and Jerusalinsky (1996), including the psychic subject. The second one is that, in autism, there are problems in the subjective constitution, which are highlighted in the manifestations observed in the school institution. This theoretical choice constitutes an attempt to escape the medical-educational model of Special Education, and the psychiatric discourse and its categories, which captures a significant range of subjects in the present days. In the operationalization of the investigation, the methodological framework was documental research, taking as object of analysis the pedagogical reports and plans of special educational services, elaborated by teachers of Special Education. In the methodological design, these documents were used as powerful narratives of the practices engendered in schools. The analysis of the data used the four theoretical axes of the Psychoanalytical Evaluation at Three Years of Age (PE3/AP3) as reference: the play and fantasy; the body and its image; the speech and the position of language; the manifestations in the face of the norms and position in relation to law. Besides the four reading operators of PE3, three new categories emerged from the narratives of the teachers during the analysis of the documents, namely, the spaces and times in the pedagogical dynamics, the figure of the professional of support, and the interaction with peers. Through the analysis of the documents, it was possible to observe that the orientations anticipated in the policies of school inclusion, of universal nature, were twisted when operationalized in school. Regarding the four axes, it was noticed that not all of them were contemplated in the narratives of the teachers, not only in the observations about the development of the students but also in the combination of school practices. In addition to that, it was verified that these axes are pertinent for carrying out the reading of the inclusion cases and may serve as guiding of the pedagogical interventions, allowing openings for the students to establish social ties and tell themselves at school and in life. It is concluded, from this study, that the school practices created in the inclusion of students with autism can be problematized through the four great theoretical axes of PE3, allowing the production of new senses in the schooling processes of these subjects.